Pemberdayaan Mutu Sumber Daya Manusia dengan ‘DETEKSI: Desa Tekan Angka Stunting’ (STMIK Dharmapala Riau, 2024)
Indonesia as a country that is currently active in improving the quality of its Human Resources has one big challenge in implementing the policies that are being developed. As a country with hundreds of millions of people, the facts on the ground show that there are many people who are malnourished and infected with congenital diseases due to a lack of knowledge related to several fields of health, which of course reduces the quality of these humans. One of the government's enemies in carrying out human resource quality improvement programs is stunting. This problem has been around for a long time among the community and until now the government is still active in fighting the problem of stunting in society. The problem of stunting was also not spared in Teluk Paman Timur Village, where it was recorded that this village had more than five childrens who were infected with stunting. Through research this problem, the researcher organizes a brief socialization with several activities to socialize the importance of fifighting the increasing number of stunting in the village. With problems explained by posyandu cadres, socialization went smoothly with satisfactory results, mothers gained knowledge about how to provide good nutrition to children to prevent contracting stunting.